Recent volatility in the price of crude oil. Issue 5 (4th May 2017) - Demirbas, Ayhan; Omar Al-Sasi, Basil; Nizami, Abdul-Sattar
ABSTRACT: Oil price volatility shows the degree of rise or fall in oil prices over time. The price of crude oil is highly influenced by the fluctuations in supply–demand gap and global macroeconomic and geopolitical conditions. The Organization of the Petroleum Exporting Countries (OPEC) plays an important role in the global oil supply and demand. The oil price volatility depends on the combined effects of invariant and variable factors. Invariant factors include feedstock prices, exploration costs, drilling costs, chemical composition of oil, production costs, distribution costs, marketing costs, and packaging and storage costs, while the variable factors include global economic activity, level of production, level of consumption, exchange value of the US dollar ($), current supply and demand, geopolitical reasons, weather-related developments, and political events. Supply factors have played a more important role than demand factors in driving the 50% drop in the oil price between mid 2014 and early 2015. This paper aims to review the historical change in the crude oil prices, control limits of the OPEC annual price per barrel from 2003 to 2015, and factors affecting the oil price volatility. As a result of the review, a mean and standard deviation for the last 13 years (2003–2015) was estimated by setting an upper limit (US $ 128.63 per barrel) with ambition that this will support the oil-producing nations in gaining large cash surplus in their fiscal budget. Similarly, a lower control limit can be set at US $ 16.97. However, this will cause a direct loss to crude oil exporters, but the impacts vary from one oil-producing country to another country.